Embryonic origin of the adult hematopoietic system: advances and questions - Medvinsky, Alexander; Rybtsov, Stanislav; Taoudi, Samir (Development (Cambridge), 2011)
Definitive hematopoietic stem cells (HSCs) lie at the foundation of the adult hematopoietic system and provide an organism throughout its life with all blood cell types. Several tissues demonstrate hematopoietic activity at early stages of embryonic development, but which tissue is the primary source of these important cells and what are the early embryonic ancestors of definitive HSCs? Here, we review recent advances in the field of HSC research that have shed light on such questions, while setting them into a historical context, and discuss key issues currently circulating in this field.